1985
DOI: 10.1017/s0022050700034483
|View full text |Cite
|
Sign up to set email alerts
|

The Resolution of the Labor-Scarcity Paradox

Abstract: Many distinguished foreign visitors to the United States in the 1850s commented on the advanced states of mechanization in manufacturing. But why, at the same time, were interest rates higher and the aggregate manufacturing capital stock lower in American than in Britain? We resolve this paradox by noting that British engineers were most impressed by only those industries which relied on skilled workers. Using production parameters estimated from 1849 census data, we develop a computable general equilibrium mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…In an earlier era, Goldin and Katz (1998) argue that factory output likely substituted for the less capital-intensive artisanal production. This is a sensible view, but it is only directly supported by a solitary study: James and Skinner (1985). They show that in 1850 capital and labor were more substitutable in manufacturing sectors that were more skill-intensive than in sectors that were less skill-intensive, though the paper does not describe how the skill intensity of the sectors was assessed.…”
Section: Historical Backgroundmentioning
confidence: 96%
See 1 more Smart Citation
“…In an earlier era, Goldin and Katz (1998) argue that factory output likely substituted for the less capital-intensive artisanal production. This is a sensible view, but it is only directly supported by a solitary study: James and Skinner (1985). They show that in 1850 capital and labor were more substitutable in manufacturing sectors that were more skill-intensive than in sectors that were less skill-intensive, though the paper does not describe how the skill intensity of the sectors was assessed.…”
Section: Historical Backgroundmentioning
confidence: 96%
“…A concern with results in Table 3 is that they are potentially driven by shifts in industry mix: that is, more less skilled workers may attract less capital intensive industries (e.g., Goldin and Katz, 1998;James and Skinner, 1985) and this would alter capital ratios. To address this, we now turn to estimates that allow us to examine within industry responses to aggregate skill mix changes, using our data on production techniques detailed by area and industry.…”
Section: Responses Of Capitalmentioning
confidence: 99%
“…New economic historians spent quite a long time trying to pin down these arguments. Eventually, it was found that the United States was able to exploit complementarities between capital and natural resources to economize on the use of skilled labour in an important subset of American manufacturing (James and Skinner 1985) and that scale economies and technological change biased in favour of capital and materials-using were pervasive in manufacturing (Cain and Paterson 1986).…”
Section: Appropriate Technologymentioning
confidence: 99%
“…Although the burden of the empirical evidence suggests that Habakkuk was mistaken in his argument that the U.S. adopted more capital-intensive methods of production than Britain (Field, 1983;James and Skinner 1985), careful examination of a number of industries does support the causal connection between labor supply and the direction of technological innovation. Rather than substituting capital for labor it appears that American innovators sought to develop ways of conserving on traditional craft skills, which were in short supply in the United States.…”
Section: Northern Labor Markets In the Nineteenth Centurymentioning
confidence: 99%